Experimental study on lithium iron sulphate as cathode for lithium ion batteries - Mohamed Zulfadli Mohamed Zainal (2017)
The ubiquitous rechargeable lithium ion battery has the highest energy density, high cyclic life and is the lightest amongst rechargeable batteries, making it suitable for portable electronic applications. Nevertheless, there is still room to improve performance and cost efficiency, through new materials. Cell efficiency can be optimized by varying the cathode and anode, constituting most of the cell’s energy density. This report investigates a new and uncommercialized cathode material — Lithium Iron Sulphate (LFS) — through characterization methods and testing of coin cells at slow discharge rate with lithium metal as the anode. The purpose is to understand the material’s degradation behavior over long cycles. A cell autopsy was done after the end of the cycles and electrode peeling was discovered, prompting the team to optimize binder content (PVDF) in coatings to learn its effect on delamination. After varying the binder content from 5% to 20% and trying another binder, the results were negative. All cells suffered capacity loss at early stage of cycling, although the cell with 15% PVDF content had a slower capacity fade. Nevertheless, the cathode material was workable. Innovatively, LFS was coupled with Fe2O3 as the anode and tested as a full-cell as this set-up was never done before. As in the case of half-cells, stability rather than conductivity was a problem in LFS, with mechanical degradation of LFS deteriorating with every cycle. This report foregrounds future investigations of Lithium Iron Sulphate behavior as it addresses issues concerning capacity degradation.